# Factorise: (i) x^{3} - 2x^{2} - x + 2 (ii) x^{3} - 3x^{2} - 9x - 5

iii) x^{3} + 13x^{2} + 32x + 20 (iv) 2y^{3} + y^{2} - 2y - 1

**Solution:**

**(i) ** Let p(x) = x^{3} - 2x^{2} - x + 2

By the factor theorem we know that x - a is a factor of p (x) if p (a) = 0.

We shall find a factor of p(x) by using some trial value of x, say x = 1.

p(1) = (1)^{3} - 2(1)^{2} - 1 + 2

= 1 - 2 - 1 + 2 = 0

Since the remainder of p(1) = 0 , by factor theorem we can say p(x) = x^{3} - 2x^{2} - x + 2 is divisible by x - 1.

Now divide p(x) by x - 1 using long division,

Hence x^{3} - 2x^{2} - x + 2 = (x -1) (x^{2} - x - 2)

Now taking x^{2} - x - 2 , find two numbers p, q such that:

p + q = co-efficient of x

p × q = product of co-efficient of x^{2} and the constant term

p + q = -1 (co-efficient of x)

p × q = 1 × (-2) = -2 (co-efficient of x^{2} and the constant term.)

By trial and error method, we get p = -2, q = 1.

Now splitting the middle term of the given polynomial,

x^{2} - x - 2 = x^{2} - 2x + x - 2

= x(x - 2) + 1(x - 2)

= (x + 1) (x - 2)

∴ x^{3} - 2x^{2} - x + 2 = (x - 1) (x - 2) (x + 1)

**Method 2:**

x^{3} - 2x^{2} - x + 2 = (x^{3} - 2x^{2}) - (x - 2)

= x^{2} (x - 2) - 1(x - 2)

= (x - 2) (x^{2} -1)

= (x - 2) (x + 1) (x - 1) (By using a^{2} - b^{2} = (a + b)(a - b) )

**(ii)** Let p(x) = x^{3} - 3x^{2} - 9x - 5

We shall find a factor of p(y) by using some trial value of y, say x = -1

p(-1) = (-1)^{3} - 3(-1)^{2} - 9(-1) - 5

= -1 - 3 + 9 - 5

= -9 + 9 = 0

Since the remainder of p(-1) = 0 , by factor theorem we can say x + 1 is a factor ofp(x) = x^{3} - 3x^{2} - 9x - 5.

Now dividing p(x) by x + 1 using long division.

Hence x^{3} - 3x^{2} - 9x - 5 = (x +1) (x^{2} - 4x - 5)

Now taking x^{2} - 4x - 5, find two numbers p, q such that:

p + q = -4 (co-efficient of x)

p × q = 1 × -5 = -5 (product of co-efficient of x^{2} and the constant term)

By trial and error method, we get p = -5, q = 1.

Now splitting the middle term of the given polynomial,

x^{2} - 4x - 5 = x^{2} - 5x + x - 5

= x(x - 5) + 1(x - 5)

= (x + 1)(x - 5)

Therefore, x^{3} - 3x^{2} - 9x - 5 = (x + 1) (x - 5) (x + 1) = (x + 1)^{2 }(x - 5)

**(iii)** Let p(x) = x^{3} + 13x^{2} + 32x + 20

We shall find a factor of p(x) by using some trial value of x, say x = -1. (Since all the terms are positive.)

p(-1) = (-1)^{3} + 13(-1)^{2} + 32(-1) + 20

= -1 + 13 - 32 + 20 = 0

Since the remainder of p(-1) = 0, by factor theorem we can say x + 1 is a factor of p(x) = x^{3} + 13x^{2} + 32x + 20.

Now dividing p(x) by x + 1 using long division,

Therefore, x^{3} + 13x^{2} + 32x + 20 = (x + 1)(x^{2} + 12x + 20)

Now taking x^{2} + 12x + 20, find two numbers p, q such that:

p + q = 12 (co-efficient of x)

p × q = 1 × 20 = 20 (product of co-efficient of x² and the constant term.)

By trial and error method, we get p = 10, q = 2.

Now splitting the middle term of the given polynomial,

x^{2} + 12x + 20 = x^{2} + 10x + 2x + 20

= x(x + 10) + 2(x + 10)

= (x + 10) (x + 2)

Therefore, x^{3} + 13x^{2} + 32x + 20 = (x + 1) (x + 10) (x + 2)

**Method 2:**

x^{3} + 13x^{2} + 32x + 20 = x^{3} + 10x^{2} + 3x^{2} + 30x + 2x + 20

= x^{2} (x + 10) + 3x(x + 10) + 2(x + 10)

= (x + 10) (x^{2} + 3x + 2)

= (x + 10) (x^{2} + 2x + x + 2)

= (x + 10) [x(x + 2) + 1(x + 2)]

= (x + 10) (x + 2) (x + 1)

**(iv)** Let p(x) = 2y^{3} + y^{2} - 2y - 1

We shall find a factor of p(y) by using some trial value of y, say y = 1.

p(1) = 2(1)^{3} + (1)^{2} - 2(1) - 1

= 2 + 1 - 2 - 1 = 0

Since the remainder of p(1) = 0, by factor theorem we can say y - 1 is a factor of p(y) = 2y^{3} + y^{2} - 2y - 1

Now dividing p(y) by y - 1 using long division,

Therefore, 2y^{3} + y^{2} - 2y - 1 = (y - 1) (2y^{2} + 3y + 1)

Now taking 2y^{2} + 3y + 1, find two numbers p, q such that:

p + q = 3 (co-efficient of y)

p × q = 2 × 1 = 2 (product of co-efficient of y^{2} and the constant term)

By trial and error method, we get p = 2, q = 1.

Now splitting the middle term of the given polynomial,

2y^{2} + 3y + 1 = 2y^{2} + 2y + y + 1

= 2y(y + 1) + 1 (y + 1)

= (2y + 1) (y + 1)

Therefore, 2y^{3} + y^{2} - 2y - 1 = (y - 1) (2y + 1) (y + 1)

**☛ Check: **NCERT Class 9 Maths Solutions Chapter 2

**Video Solution:**

## Factorise: (i) x³ - 2x² - x + 2 (ii) x³ - 3x² - 9x - 5 (iii) x³ + 13x² + 32x + 20 (iv) 2y³ + y² - 2y - 1

NCERT Solutions Class 9 Maths Chapter 2 Exercise 2.4 Question 5:

**Summary:**

The factorized form of x^{3 }- 2x^{2} - x + 2, x^{3 }- 3x^{2} - 9x - 5, x^{3 }+ 13x^{2} + 32x + 20, 2y^{3 }+ y^{2} - 2y - 1 are (x - 1)(x - 2)(x + 1), (x + 1)^{2}(x - 5), (x + 10)(x + 2)(x + 1) and (y - 1)(2y + 1)(y + 1) respectively.

**☛ Related Questions:**

- Determine which of the following polynomials has (x + 1) a factor:i) x3 + x2 + x + 1ii) x4 + x3 + x2 + x + 1iii) x4 + 3x3 + 3x2 + x +1iv) x3 - x2 - (2 + √2)x + √2
- Use the Factor Theorem to determine whether g(x) is a factor of p(x) in each of the following cases:(i) p(x) = 2x3 + x2 - 2x - 1, g(x) = x +1(ii) p(x) = x3 + 3x2 + 3x + 1, g(x) = x + 2(iii) p(x) = x3 - 4x2 + x + 6, g(x) = x - 3
- Find the value of k, if x - 1 is a factor of p(x) in each of the following cases: (i) p(x) = x2 + x + k (ii) p(x) = 2x2 + kx + √2 (iii) p(x) = kx2 - √2x + 1 (iv) (x) = kx2 - 3x + k

visual curriculum